Mysterious journeys, episode I - Zimmerman, Ron.; Jones Evan Jason; Lovett, Marcus; Mike Methis Productions, Inc. for Travel Channel; Magna Vision (Bethesda, MD distributed by Discovery Channel Video ; distributed in the Philippines by MagnaVision, 2003)
Travel the Earth to visit the sites that have played host to alien visitors. Reports of extraterrestrial visitors span human history and have come from all corners of the globe. Some places such as Roswell, New Mexico, have based their entire identity around their brush with the intergalactic. Mysterious Journeys takes you to these locations and investigates the fascinating and eerie stories that surround them.
Editor, Sue Hoskins ; music, Robert Boress ; Associate producer, Kurt Krutzen; Segment producers, Josh Finn, Gillian Sonnier; Field producer, Nellie Zimmerman; Camera, Ron Zimmerman; Audio, Nellie Zimmerman; Assistant editor, Josh Finn; Production assistant, Tom Shannon; Post production supervisor, Kurt Knutzen; Online editors, Keith Glispie, Marcus Juniel
Narrated by Marcus Lovett.
VCD.
Keywords: Extraterrestrial beings